2022
DOI: 10.1021/acs.jpcc.2c00593
|View full text |Cite
|
Sign up to set email alerts
|

Micro-to-Nano Bimodal Single-Particle Sensing Using Optical Tweezers

Abstract: Recently, electrical sensing techniques for single objects, such as nanoparticles, biomolecules, and viruses, have attracted a great deal of attention. To achieve both high throughput and high measurement accuracy, target objects need to be quickly transported to a small sensing section embedded in a fluidic channel. In the present study, we propose a novel method to improve the signal-to-noise (S/N) ratio of electrical signals of single particles, using optical tweezers and a microchannel. Optically trapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Optical and electrochemical sensing strategies integrated with discrimination capability for the particle size and type represent a growing field. , In particular, different optical and/or electrochemical platforms were developed for this purpose. For instance, the coupling between optical tweezers and ML was demonstrated for microplastics classification in terms of both size and material . However, this approach was not proven for plastic nanoparticles and requires an expensive and complex experimental setup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical and electrochemical sensing strategies integrated with discrimination capability for the particle size and type represent a growing field. , In particular, different optical and/or electrochemical platforms were developed for this purpose. For instance, the coupling between optical tweezers and ML was demonstrated for microplastics classification in terms of both size and material . However, this approach was not proven for plastic nanoparticles and requires an expensive and complex experimental setup.…”
Section: Discussionmentioning
confidence: 99%
“… 53 However, this approach was not proven for plastic nanoparticles and requires an expensive and complex experimental setup. Along this line, Doi et al 54 demonstrated the use of optical tweezers to distinguish nano- and microparticles but without the discrimination of the material type. A very recent work 55 proposes a sensing approach by hyperspectral stimulated Raman scattering (SRS) microscopy, demonstrating the nanoplastics classification in terms of different materials in water samples, 55 but in this case too, the approach requires complex and expensive instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…To separate the sample and reference solutions, nanochannels were used. The composite structure of micro- and nanochannels is effective in focusing strong electric fields on the nanochannel, which serves as the sensing region [ 39 ]. Three types of nanochannels were prepared for pH sensors, and their cross-sectional views are depicted in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we reported a possibility of electrohydrodynamic flows induced by electrokinetic transport through ion-exchange membranes. It was experimentally and theoretically determined that selective ion transport could drive a liquid flow under an applied voltage of a few volts in aqueous solutions. Especially in nanochannels, electroosmotic flows (EOFs) effectively worked to transport and transform nanoobjects, e.g., deoxyribonucleic acid (DNA) , and nanoparticles. Focusing on ionic current responses, the detailed properties of target objects and liquids were clarified. Here, it is important to measure ion concentrations and electric fields locally in liquids.…”
Section: Introductionmentioning
confidence: 99%